An oleaginous supplement to improve the nutritional quality of goat's milk and cheese (whole or extruded linseed, rapeseed cake) - Delmotte C.; Rondia P.; Dehareng F.; Laloux J.; Famerée J. (Nutritional and foraging ecology of sheep and goats, 2009)
Extruded linseed supplement is widely used to improve the nutritional quality of ruminant products by increasing the percentage of the polyunsaturated (PUFA), the omega 3 and the conjugated linoleic (CLA) fatty acids. In order to decrease costs and environmental impacts of treatment and of transport, it would be interesting to privilege the native linseed and/or local sources in unsaturated fatty acids such as rapeseed cake. This work studied the effects of a linseed (whole and extruded forms) and of a rapeseed cake supplement on fatty acid composition of goat milk and cheeses. The diet did not affect the milk yield or the milk fat and protein content. The cheese-making outputs were also similar. The milk fatty acid composition showed that the bio-hydrogenation was less complete with the extruded linseed and increased the PUFA, omega 3 and CLA contents. However, whole seed could be digested and similar modifications induced. The rapeseed cake induced significantly less saturated fatty acids and a high CLA content. It also seemed to maintain conditions in the rumen that limit hydrogenation. Lastly, cheese-making and refining did not alter the fatty acid composition.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)